2015
DOI: 10.3748/wjg.v21.i21.6621
|View full text |Cite
|
Sign up to set email alerts
|

Low RASSF6 expression in pancreatic ductal adenocarcinoma is associated with poor survival

Abstract: Patient-derived xenograft (PDX) tumors are powerful tools to study cancer biology. However , the ability of PDX tumors to model the biological and histological diversity of pancreatic ductal adenocarcinoma (PDAC) is not well known. In this study, we subcutaneously implanted 133 primary and metastatic PDAC tumors into immunodeficient mice. Fifty-seven tumors were successfully engrafted and even after extensive passaging, the histology of poorly-, moderately-, and well-differentiated tumors was maintained in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…45,46 The expression of RASSF6 was downregulated in several tumours such as gastric cancer, hepatocellular carcinoma, colorectal cancer and pancreatic ductal adenocarcinoma. [47][48][49] RASSF6 played as a tumour suppressor gene and suppressed tumour cell growth, invasion and migration and promoted the cell cycle and apoptosis. 48,50 In this study, we demonstrated that RASSF6 expression was downregulated in osteosarcoma tissues and cell lines and downregulated expression of RASSF6 was correlated with advanced TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 The expression of RASSF6 was downregulated in several tumours such as gastric cancer, hepatocellular carcinoma, colorectal cancer and pancreatic ductal adenocarcinoma. [47][48][49] RASSF6 played as a tumour suppressor gene and suppressed tumour cell growth, invasion and migration and promoted the cell cycle and apoptosis. 48,50 In this study, we demonstrated that RASSF6 expression was downregulated in osteosarcoma tissues and cell lines and downregulated expression of RASSF6 was correlated with advanced TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…Humans have six C‐RASSFs, all of which are known as tumor suppressors (Avruch et al., ; Volodko, Gordon, Salla, Ghazaleh, & Baksh, ). RASSF6 is frequently suppressed by DNA hypermethylation in human cancers, and its low expression correlates with tumor progression and short disease‐free survival (Chen et al., ; Djos, Martinsson, Kogner, & Carén, ; Guo et al., ; Hesson et al., ; Liang et al., ; Richter, Pfeifer, & Dammann, ; Richter, Zimmermann, Haag, Walesch, & Dammann, ; Wen et al., ; Ye et al., ). These findings support that RASSF6 is a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent work also detected low expression of RASSF6 (Ras association domain family 6) in PDAC and associated it with poor survival [132]. Only 16.7% of patients’ tumor tissues were strongly positive for RASSF6 in immunostainings.…”
Section: Disorders Of Apoptosismentioning
confidence: 99%